2018
DOI: 10.1158/0008-5472.can-17-3018
|View full text |Cite
|
Sign up to set email alerts
|

High USP6NL Levels in Breast Cancer Sustain Chronic AKT Phosphorylation and GLUT1 Stability Fueling Aerobic Glycolysis

Abstract: USP6NL, also named RN-tre, is a GTPase-activating protein involved in control of endocytosis and signal transduction. Here we report that USP6NL is overexpressed in breast cancer, mainly of the basal-like/integrative cluster 10 subtype. Increased USP6NL levels were accompanied by gene amplification and were associated with worse prognosis in the METABRIC dataset, retaining prognostic value in multivariable analysis. High levels of USP6NL in breast cancer cells delayed endocytosis and degradation of the EGFR, c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 45 publications
1
52
0
Order By: Relevance
“…GLUT1, a major glucose transporter protein, was upregulated in various tumor cells. 43,44 It should be noted that significantly reduced concentrations of glucose were observed in S100A2 knockout cells, whereas S100A2 overexpression cells exhibited higher levels than controls. In this study, we also proved that inhibited GLUT1 could abrogate S100A2-enhanced proliferation and glycolysis in colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…GLUT1, a major glucose transporter protein, was upregulated in various tumor cells. 43,44 It should be noted that significantly reduced concentrations of glucose were observed in S100A2 knockout cells, whereas S100A2 overexpression cells exhibited higher levels than controls. In this study, we also proved that inhibited GLUT1 could abrogate S100A2-enhanced proliferation and glycolysis in colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…GLUT1 overexpression is significantly correlated with TNBC, and it promotes TNBC cell proliferation and invasion (38,39). Notably, serine/threonine kinase AKT stabilizes GLUT1 at the cell membrane by perturbing its endocytosis, therefore promoting aerobic glycolysis (41).…”
Section: Glycolysismentioning
confidence: 99%
“…USP6NL, a GTPase-activating protein involved in signal transduction regulation, is often overexpressed in basal-like TNBC. Knockdown of USP6NL impairs epidermal growth factor receptor (EGFR)/AKT signaling and promotes GLUT1 degradation, thus suspending cell proliferation exclusively in aggressive basal-like TNBC tumors harboring USP6NL overexpression (41).…”
Section: Glycolysismentioning
confidence: 99%
“…Additionally, Rab5 was shown to participate in adenovirus endocytosis (Rauma et al, 1999), both Rab5a and Rab5b were found to play functional roles in web formation and viral genome replication during HCV (hepatitis C virus) infection (Stone et al, 2007), and Rab5a was identied as a crucial target of HBV (hepatitis B virus) during HBV-related hepatocellular carcinoma pathogenesis (Sheng et al, 2014). been proposed as a potential therapeutic target for these types of breast cancer (Avanzato et al, 2018). This protein also plays a functional role in infection, as it was shown to regulate the uptake and intracellular tracking of Shiga toxins (Fuchs et al, 2007).…”
Section: Details Of Mcmcmentioning
confidence: 99%